Description of patients presenting with mental illness in emergency medical services: a retrospective observational study - Natalie Bergman; Aleksandra Jarling; Gabriella Boysen Norberg; Beatrice Alenljung; Magnus Hagiwara Andersson (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine)
Abstract Background Mental illness is prevalent worldwide, creating a demand for Emergency Medical Service (EMS) assessments in mental illness, yet research on the epidemiology of patients with mental illness in the EMS is lacking in Sweden. This study aims to describe the patients presenting with symptoms of mental illness in the EMS and how they are assessed in the prehospital setting. Method A retrospective observational study was conducted to identify patients assessed for symptoms of mental illness in the EMS in 2023. A total of 1,304 records met the inclusion criteria and were included in the study: [1] assessed in the EMS due to symptoms of mental illness and [2] over 13 years old. The data were analysed using IBM SPSS Statistic 28. Results More females (54.3%) than men (45.7%) were assessed for mental illness (p = < 0.01). The median age was 39 years, with an interquartile range (IQR) of 32 years (p = < 0.01) and a total range of 13–91. Most patients were assessed once, with a range of 1 to 37 times. The initial priority of the patients was mainly Priority 1 (45.6%) or Priority 2 (49.9%). However, this shifted after the EMS assessment where most patients either recieved a lower priority or No priority [due to not being transported] (39.7%). The most common triage colour was Orange (21.4%), indicating the need for acute care, but four out of ten patients did not recieve a triage color (40.4%). The most frequent patients assessed by the EMS were suicide threats/attempts (45.2%) and intoxications (48.8%) with intoxication cases most likely to be hospitalised. The length of the stay in the hospital varied from 0 to 67 days but most patients were discharged within 24 h (6.8%) or admitted for 24 h (6.4%). Conclusion Patients with mental illness are frequently assessed in the EMS, primarily for suicide threats/attempts and intoxication. However, few are admitted to the hospital, and many are not triaged, suggesting difficulties in referring patients with mental illness to the right level of care. The result may inform future studies assessing patients with mental illness in the EMS.